The analysis of biomechanics on footwork step pattern spike toward power spike of volleyball sport - Santoso, Danang Ari; Setiabudi, Moh. Agung (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2019)
Biomechanics is a science field that studies movement which can later be used as a reference for movement technique in sports. Volleyball has spike, block, service, and passing techniques. Basically, spike technique is started with a starting step then jumping. Variable spike step pattern (footwork) will cause different performance. This study aimed to get a step pattern in creating the best spike performance. This research was carried out by using experimental method. The research design used was one shot case study. The varied initial step patterns were A, B, C, and D patterns. The subject of this study was volleyball athletes of PGRI Banyuwangi University. The data collection was done in 5 replications for the starting step patterns. Then, the data was processed by using kinovea software to analyze spike performance. The results showed that the best power performance occurred in the A starting step pattern which was 115.717 J / dt while the minimum power performance occurred in the B starting step pattern which was 93,098 J / dt. This was due to a change in force (F) in the starting step in each step pattern. In the A and D patterns, the force (F) tended to increase while in B and C patterns, the force (F) decreased in the last step because there was a change in the direction of movement or a step deviation. Thus, the power performance decreased.